A Survey of Linezolid Prescription Before and After Protocol Implementation in a Teaching Hospital - Sheyda Najafi; Hedieh Keshavarz-Bahaghighat; Aarefeh Jafarzadeh Kohneloo; Jalil Makarem; Zahra Jahangard-Rafsanjani (Research Center for Rational Use of Drugs (RCRUD), 2018)
Background: Linezolid has been recognized as a safe and effective medicine against a wide variety of Gram-positive pathogens. Purpose: The primary objective of this study was to assess utilization appropriateness of linezolid and explore the efficiency of protocol intervention to proceed to rational drug usage. Method: The project was conducted in a referral teaching hospital from September 2015 to January 2017 in two phases. In the first step, a six-month survey was performed to evaluate the prescribing appropriateness of linezolid. Patients receiving linezolid were identified using hospital IT system and the medical charts were analyzed based on accurate indications and duration of linezolid prescription. Subsequently, a restrictive protocol was developed and communicated after a consensus by Drug and Therapeutics Committee in May 2016. After introduction of the protocol, an active daily surveillance of patients was done by hospital pharmacists. The appropriateness of linezolid utilization and infectious consultations were compared before and after protocol implementation. Results: In the first phase of the study, the indication of linezolid was appropriate in 56.2% of cases and improved considerably to 68.6% (P value: 0.04) after protocol enforcement. Furthermore the duration of the linezolid consumption was correct in 66.6% of patients, increasing to 88.5% after protocol introduction (P value 0.07). In the first step, 56.9% of linezolid prescriptions were based on infectious disease consultation which enhanced remarkably to 87.5% in the second step (P value 0.001), while, 65.5% and 73.8% of these consultations were appropriate in the study surveys respectively. Conclusion: The protocol intervention could improve appropriate prescribing of linezolid in the hospital setting. However, ongoing audit studies are recommended to maintain the rational prescription of linezolid.